2022
DOI: 10.1109/access.2022.3140488
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of an Autonomous Tracking System for Localization of Radio-Tagged Flying Insects

Abstract: The tracking of flying insects is one of the main challenges in the field of ecosystem and biodiversity protection. In the case of invasive insects such as Asian hornets, extensive considerations must be made in estimating the habitat because of the limitations of available sensors and environmental uncertainty. In this study, we propose an approach for localizing and autonomously tracking radio-tagged flying insects and developing an unmanned aerial vehicle (UAV)-based robotic system. The extended Kalman filt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…In a previous study [45], we attempted to track radio-tagged flying insects by using a single directional antenna. However, this method had limitations, including the need for rotation time and low tracking accuracy.…”
Section: Problem Descriptionmentioning
confidence: 99%
“…In a previous study [45], we attempted to track radio-tagged flying insects by using a single directional antenna. However, this method had limitations, including the need for rotation time and low tracking accuracy.…”
Section: Problem Descriptionmentioning
confidence: 99%
“…Recently, with the increase in environmental pollution, the need for management systems that can effectively manage natural systems and ecosystems has emerged. [1][2][3][4] Furthermore, in agriculture, a system to minimize environmental damage and manage it is being studied. 5,6 Among the environmental management systems, data obtained from satellite maps of the natural environment of tributaries are used for water quality management.…”
Section: Introductionmentioning
confidence: 99%
“…Since it was reported that it was used in the investigation of American alligators and waterfowl in 2006 [16], UAVs made some progress in animal identification, tracking [17,18], size measurement [19] and behavior investigation [18,20]. Due to the low cost of UAV images and the fact that the resolution can be adjusted according to the altitude (up to 2 mm), UAV images can be used to identify large animals such as African elephants, giraffes [18], manatees [17], cattle, and sheep [21], as well as animals as small as penguins, albatross cubs [22], Canadian geese [23], and even flying insects such as bumblebees [24].…”
Section: Introductionmentioning
confidence: 99%